The Examination of Recency and Knowledge Effect in Stock Investment Decision Making: an Experimental Study - LIZA ALVIA; DEDHY SULISTIAWAN (The Indonesian Journal of Accounting Research, 2013)
This research is the combination of Hogarth and Einhorn (1992) and Dilla and Steinbart (2005) studies. The purpose of this study is to examine recency and knowledge effects in the stock investment decision making when mixed information (fundamental and technical information) is sequentially presented. Using a laboratory experimental design, the results show that (1) there is recency effect when different information (based on type and content) is sequentially presented; (2) based on technical analysis information, there is a difference in the stock investment decision making between the treatment and the control groups. Contrary to the expectation, there is no different stock investment decision resulted from fundamental analysis information. The results show that decision makers with accounting background tend to use only financial information, while those who understand technical analysis will consider both fundamental and technical data analysis.